2008
DOI: 10.1210/en.2008-1027
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Inhibits Basal and Gonadotropin-Releasing Hormone Induction of Luteinizing Hormone β-Subunit Gene Expression

Abstract: LH and FSH play critical roles in mammalian reproduction by mediating steroidogenesis and gametogenesis in the gonad. Gonadal steroid hormone feedback to the hypothalamus and pituitary influences production of the gonadotropins. We previously demonstrated that progesterone differentially regulates the expression of the LH and FSH beta-subunits at the level of the gonadotrope: FSHbeta transcription is induced, whereas LHbeta is repressed. In this study, we investigated the mechanism of progesterone repression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 40 publications
0
16
0
3
Order By: Relevance
“…The Ϫ1800 rat Lhb-luc reporter in pGL3 was provided by Dr. Mark Lawson. Construction of 5Ј truncations of the Ϫ1800 Lhb-luc reporter plasmid (Ϫ500, Ϫ300, Ϫ150, Ϫ87) was previously described (63). The Ϫ1068/ϩ9 human LHB-luc reporter in pA3 was generously provided by Dr. Daniel Bernard.…”
Section: ␤-Gal Staining Of Lhb-cre X Rosa26mentioning
confidence: 99%
“…The Ϫ1800 rat Lhb-luc reporter in pGL3 was provided by Dr. Mark Lawson. Construction of 5Ј truncations of the Ϫ1800 Lhb-luc reporter plasmid (Ϫ500, Ϫ300, Ϫ150, Ϫ87) was previously described (63). The Ϫ1068/ϩ9 human LHB-luc reporter in pA3 was generously provided by Dr. Daniel Bernard.…”
Section: ␤-Gal Staining Of Lhb-cre X Rosa26mentioning
confidence: 99%
“…After ovulation, a progressive increase of P4 secretion from corpora lutea produces a negative feedback over GnRH secretion [3,4]. In addition, P4 also acts in the pituitary gland by repressing luteinizing hormone (LH) expression in a receptor-dependent manner [5]. If fertilization takes place following ovulation, P4 levels increase progressively, modulating blastocyst implantation, and remain elevated throughout the ensuing pregnancy [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Because androgen stimulation in the presence of the endogenous L␤T2 AR is relatively weak, several of these studies have amplified the steroid hormone response by cotransfecting AR expression constructs, a method we have adopted in the current study. The same strategy has been employed to study ER, PR, and GR in L␤T2 cells (35,36,52,68,69). In the studies reported here, the rPACAP promoter was robustly activated by androgen in the context of the immortalized L␤T2 gonadotrope, with activation that is dependent on the presence of AR.…”
Section: Discussionmentioning
confidence: 98%